2018
DOI: 10.1111/jch.13300
|View full text |Cite|
|
Sign up to set email alerts
|

The importance of pulse pressure on cardiovascular risk and total mortality in the general population: Is sex relevant?

Abstract: The aim of the present study is to investigate the predictive value of pulse pressure (PP) on cardiovascular events in the general population and in both sexes, separately. The study involved 2045 participants from the PAMELA study who underwent 24-hour ambulatory blood pressure (BP) monitoring. The participants were followed from the initial medical visit for a time interval of 137 ± 23 months. It was found that office, home, and 24-hour blood pressures were significantly higher in the individuals who experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…Recently, Tadic and coworkers 17 found out that 24‐h PP and daytime PP predicted CV events and mortality in a general population of wide age range, but nighttime PP was significant only in men. Earlier, 24‐h, daytime and nighttime PP were recognized as better prognostic factors for CV events in a group of 60 years of age or older, compared with a younger group 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Tadic and coworkers 17 found out that 24‐h PP and daytime PP predicted CV events and mortality in a general population of wide age range, but nighttime PP was significant only in men. Earlier, 24‐h, daytime and nighttime PP were recognized as better prognostic factors for CV events in a group of 60 years of age or older, compared with a younger group 28 .…”
Section: Discussionmentioning
confidence: 99%
“… 16 In a population study, daytime and 24‐h PP had a predictive value in the general population, whereas the nighttime PP was a risk factor for men. 17 In a large study consisting of 11 different populations, all individuals within the highest 24‐h PP distribution had an elevated risk for CV events, and those over 60 years had the higher all‐cause mortality than those below. 18 In some studies, however, there has been controversy over significance of ambulatory PP as a predictor for CV and all‐cause mortality.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, a high TWA PP in the early phase of septic shock showed an independent association with 28-day mortality. High PP is a strong predictor of cardiovascular morbidity/mortality in the geriatric population and among patients with hypertension, coronary heart disease, diabetes mellitus, and renal disease [16][17][18][19][20]. However, there is a paucity of studies about the prognostic value of PP in regards to mortality of patients with sepsis, especially among patients administered a resuscitation therapy bundle including maintaining MAP at > 65 mmHg [21].…”
Section: Discussionmentioning
confidence: 99%
“…However, a high proportion of older adults have isolated systolic hypertension, which is significantly associated with mortality . It is important to analyze the role of office and 24-hour pulse pressure in the prediction of mortality …”
mentioning
confidence: 99%